Development of an Online Hotel Reservation System in Sri Lanka using Cutting-Edge Technologies - C.P.U Jayawardena; T.I.S Senaweera; G.S Weeratunga; K.A.P.M Perera; D. I. De Silva; S. Vidhanaarachchi (International Journal of Engineering and Management Research, 2022)
The hotel management system is an important aspect of contemporary hotel life since it assures the hotel's correct operation, making it efficient and enabling the opportunity to reserve a room online. It contains information on the rooms and the hotel as a whole for the staff and administration. This technology eliminates the majority of the paperwork, making it a must-have tool for any modern hotel. The present reservation system is analyzed and improved. The purpose of this paper is to offer a thorough examination of the system. Make an effort to enhance the existing condition in the hotel management industry. In addition, a modest prototype built using cutting-edge technologies MongoDB, Express.js, React.js, and Node.js (MERN stack) will be discussed. This will showcase how the system would operate from the client and administrator sides. The MERN stack is an excellent choice for hotels wishing to develop high-quality web applications. In fact, this stack enables the rapid development of online applications and software in addition to leveraging high-performance and customized technologies. The mentioned system was shown to be significantly more affordable, an open-source program with superior performance, and UI rendering by using these technologies. In addition to assessing the value of an online reservation system for Sri Lanka's hotel industry, this paper will examine how the environment's components should be set up, integrated, and built, as well as how the requirements, design, construction, and test phases of the application development lifecycle should be combined to create an overall system and how a developer would actually go about creating applications that would be used in practical situations.